2018
DOI: 10.3319/tao.2017.11.29.01
|View full text |Cite
|
Sign up to set email alerts
|

Changes of tropical precipitation and convective structure under global warming projected by CMIP5 model simulations

Abstract: Regional changes of precipitation intensity, convective structure and column water vapor (CWV) in the Tropics are examined using climate model simulation outputs archived in the Coupled Model Intercomparison Project, phase 5 (CMIP5) for the representative concentration pathway 8.5 (RCP8.5) experiments. Under global warming, CWV increases homogeneously in space following the Clausius-Clapeyron scaling. In contrast, precipitation changes exhibit marked regional discrepancies with a mix of positive and negative a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Interestingly, recent studies have revealed a strong connection between ENSO and explosive eruptions, suggesting that eruptions may induce El Niño (Pausata et al, , ) or La Niña (D'Arrigo et al, ; McGregor & Timmermann, ) like anomalies. It has been discussed in numerous studies that explosive volcanic eruption provides suitable conditions that may trigger ENSO phenomenon (Emile‐Geay et al, ; Liu et al, ; Liu et al, ; Maher et al, ; Ohba et al, ; Predybaylo et al, ). Moreover, studies have also indicated that ENSO impacts are very important, especially in the monsoon regions (Ashok et al, , ; Azharuddin & Dogar, ; Dogar et al, ; Dogar et al, ; Shukla, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent studies have revealed a strong connection between ENSO and explosive eruptions, suggesting that eruptions may induce El Niño (Pausata et al, , ) or La Niña (D'Arrigo et al, ; McGregor & Timmermann, ) like anomalies. It has been discussed in numerous studies that explosive volcanic eruption provides suitable conditions that may trigger ENSO phenomenon (Emile‐Geay et al, ; Liu et al, ; Liu et al, ; Maher et al, ; Ohba et al, ; Predybaylo et al, ). Moreover, studies have also indicated that ENSO impacts are very important, especially in the monsoon regions (Ashok et al, , ; Azharuddin & Dogar, ; Dogar et al, ; Dogar et al, ; Shukla, ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their fine grid spacing, important processes such as large‐scale condensation, land‐sea interaction, and topographical forcing are better resolved in high‐resolution GCMs (Boyle & Klein, ; Lau & Ploshay, ; Harris et al, ). Recent studies further emphasized that the regional convective structure and precipitation change are very sensitive to the model horizontal resolution (Bui et al, ; Liu, Yu, & Chen, ). HIRAM model has been previously used effectively to simulate aerosol's direct radiative and circulation impacts (Bangalath & Stenchikov, ; Dogar, ; Dogar & Sato, ; Dogar & Shahid, ; Dogar, Stenchikov, et al, ; Osipov et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In connection with the long-term trend of floods in low latitude regions of East Asia, previous studies suggested that the precipitation in this region will significantly increase in the future period (Lau et al 2013;Kent et al 2015). This may be caused by both of the "richget-richer" mechanism of water vapor and the changes in tropical dynamics such as strengthening of convection from the global warming (Liu et al 2018). Because it is known that the increases in carbon dioxide could directly strengthen the factors above (Bony et al 2013), this weakening tendency of floods under NIER scenarios compared to under RCP8.5 may be another robust reference to the necessity of greenhouse gas emissions reduction.…”
Section: Resultsmentioning
confidence: 99%
“…The time period between 1960-2005 was used as a historical baseline, and data between 2006-2100 underwent statistical downscaling, which was carried using spatial interpolation and bias correction using the ECDF methods utilized in the previous project phase. For dynamical downscaling, in addition to the MRI model, a high-resolution atmospheric model (HiRAM C384) [21][22][23][24][25][26][27][28][29][30][31] developed by the Geophysical Fluid Dynamics Laboratory (GFDL) was also used for cross-comparison, with a resolution of 25 km, baseline period of 1979-2003, simulating projections during 2039-2065 and 2075-2099 using the RCP8.5 scenario. These models were coupled with WRF to assess the impact of extreme and typhoon events in the context of topics such as flooding and landslides.…”
Section: Development Of Climate Projectionmentioning
confidence: 99%